1985
DOI: 10.1590/s0006-87051985000100038
|View full text |Cite
|
Sign up to set email alerts
|

Análise do pólen em dezoito cultivares de macieira

Abstract: Como subsídio essencial ao projeto de melhoramento genético da macieira (Malus spp.) por hibridação e ao conhecimento da polinização natural nas condições do Estado de São Paulo, efetuaram-se estudos sobre a quantidade e a viabilidade do pólen existente em dezoito cultivares de maior interesse no momento. Constatou-se que, entre os cultivares mais utilizados nos cruzamentos, Anna, Brasil, Dulcina, Ein Shemer, Gala, Rainha e Valinhense, juntamente com as novas seleções - IAC 170-1 e IAC 570-38 - foram os que se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…These values are clearly lower than in other fruit plants, mainly in allogamous species. Dall'Orto et al (1985) observed an average of 2700 pollen grains per anther in 18 apple cultivars.…”
Section: Resultsmentioning
confidence: 95%
“…These values are clearly lower than in other fruit plants, mainly in allogamous species. Dall'Orto et al (1985) observed an average of 2700 pollen grains per anther in 18 apple cultivars.…”
Section: Resultsmentioning
confidence: 95%
“…The hierarchical cluster based on pollen quantity and germination rate showed that 65 litchi cultivars could be classified into six clusters, and 41.54% of litchi cultivars ranged between 3830 and 4730 pollen grains per anther. The number of pollen grains per anther ranged between 1170 and 3800 in 18 apple cultivars grown under subtropical conditions in São Paulo, Brazil, and the pollen grains per flower ranged between 23,000 and 74,000 (Campo Dall'Orto et al, 1985). On an average, Brazilian apple cultivars, such as Baronesa, Suprema, Imperatriz, Lisgala, Joaquina, Princesa, Fred Hough, Daiane, Catarina, Primícia, Duquesa and Condessa produce 16-20 anthers, and a variable number of pollen grains per flower ranging between 53,000 and 103,700 were found.…”
Section: Discussionmentioning
confidence: 99%